Longitudinal associations between different types of screen use and depression and anxiety symptoms in adolescents - Mougharbel, Fatima; Chaput, Jean-Philippe; Sampasa-Kanyinga, Hugues; Colman, Ian; Leatherdale, Scott T.; Patte, Karen A.; Goldfield, Gary S. (Frontiers in Public Health, 2023)
Background: Evidence examining the longitudinal associations between different types of screen behaviours and mental health among adolescents is limited. The present study examined the association between five types of screen behaviours and symptoms of anxiety and depression one year later. Also, we assessed how changes in screen time were associated with changes in anxiety and depressive symptoms and whether the observed relationships were moderated by sex. Methods: Longitudinal data of 17,174 students in grades 9-12 (53.5% females; mean age: 15.1 ± 0.9 years) attending high schools in Canada from two waves (Year 6: 2017/18, Year 7: 2018/19) of the COMPASS study were analyzed. Leisure screen time and mental health measures were self-reported. To test if the associations between screen time and anxiety, and depression vary by sex, two-way interactions were examined for sex. Analyses accounted for school clustering, race/ethnicity, sex, age, income, body mass index z-score, and previous year anxiety and depression symptoms. Results: There were significant longitudinal associations between time spent on each type of screen and subsequent anxiety and depression symptoms. The strength of the associations varied by type of screen behaviour. Interaction analysis indicated a sex difference for television viewing and anxiety and depression symptoms, and internet surfing and anxiety symptoms. A dose-response relationship was observed between phone talking and anxiety symptoms. Beta estimates indicated that an increase in screen duration was associated with a further increase in anxiety and depression symptoms. Conclusion: Higher screen time was longitudinally associated with higher anxiety and depression symptoms at 1-year follow-up in adolescents. Time-change associations between screen usage and depressive and anxiety symptoms were observed. Also, associations differed based on sex and scree-type, whereby greater increases in screen use predicted greater emotional distress. Findings from this prospective analysis suggest that screen time is an important determinant of anxiety and depressive symptoms among adolescents. Future studies are recommended to help inform programs promoting screen time reduction with a goal to enhance adolescents’ mental health.